The first Pushkin translations into Lithuanian - Sideravičius, R. (Literatūra, 1969)
Pushkin's influence on Lithuanian poetry is undoubtful. But this influence, as it is acknowledged by a lot of people investigating this problem, is difficult to formulate. In spite of the copious material on Pushkin's influence upon Lithuanian literature, we still lack more precise and generalizing conclusions.The article deals with one aspect of the interrelation between those two literatures, that is with translations and, first of all, that which interests Lithuanian poets in Pushkin's work. Having analysed the features of the works chosen for translation, it becomes clear that these were realistic and the most national works of the great poet. The article deals with newly discovered translations published in 1875 as well. Alongside this, some concrete problems of translation are being analysed, e.g., the importance of the translation work on the formation of the syllabic-accentual Lithuanian verse and Lithuanian poetry as a whole.
Keywords: -